Combined Treatment of Old Sanitary Landfill Leachate - Visnja Orescanin; Robert Kollar; Damir Ruk; Ivan Halkijevic; Marin Kuspilic (Hamadan University of Medical Sciences, 2016)
Landfill leachate presents hardly treatable, highly complex and very toxic environmental effluent originated in the municipal solid waste degradation process. Although, numerous treatment methods were developed so far, none of them alone could achieve permissible limits of the primary pollutants to discharge into natural recipients. The current study aimed to develop and apply the process to treat landfill leachate by simultaneous application of electrochemical methods, ultrasound, electromagnetic field and ozonation to achieve the legal criteria for its discharge into natural recipient and minimize its adverse environmental impacts. For this purpose, old landfill leachate was taken from the Piskornica (Koprivnica, Croatia) sanitary landfill. Prior to the treatment, the leachate was supplemented with NaCl (2 g/L) and subjected to simultaneous treatment with stainless steel electrode plates, ultrasound and recirculation through electromagnetic field. After 45 minutes, stainless steel electrode plates were replaced by iron electrodes and treated for another 10 minutes followed by 15 minutes of the treatment with aluminum electrode plates. Ultrasound and recirculation through electromagnetic field were also applied during Fe and Al electrode treatment. Finally, the electrodes were removed and the suspension was mixed with ozone for another 30 minutes and allowed to settle for an hour. Following the combined treatment, the removal efficiency for the turbidity, color, suspended solids, ammonium, phosphates and heavy metals was 99% or higher, while the removal of COD was 97%. All the measured parameters in the treated leachate were lower compared to upper permissible limit for discharge into natural recipient.